OPTIMALISASI MANAJEMEN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN MUTU PENDIDIKAN DI SEKOLAH ISLAM SWASTA - Fahmi Fikri (As-Sulthan Journal of Education, 2025)
This study aims to analyze the optimization of human resource management in the development of educational quality in private Islamic schools. Human resource management is a crucial aspect in improving the quality of educational institutions, as the success of the educational process is highly influenced by the quality of teachers and educational staff. This research employs a qualitative approach using library research by examining various sources of literature such as books, journal articles, and relevant academic documents related to the research topic. The data analysis technique used is descriptive qualitative analysis by identifying, classifying, and interpreting various concepts and theories related to human resource management in education. The results of the study indicate that the optimization of human resource management in Islamic educational institutions can be achieved through proper planning, selective recruitment processes, the development of teacher competencies, objective performance evaluation systems, and the strengthening of school leadership. Effective human resource management also contributes to increasing teacher professionalism, creating a conducive learning environment, improving the quality of educational services, and strengthening Islamic values within the educational process. Therefore, optimal human resource management becomes a strategic factor in supporting sustainable educational quality improvement in private Islamic schools.